Argumentum ad hominem – good argument or fallacy? An analysis of Croatian parliamentary debate - Kišiček, Gabrijela (2017)
Traditionally, logic textbooks treated ad hominem argument as fallacious and dismissed it as logically unacceptable. This general assumption changed with the work of Johnstone (1952) who showed that there are examples in which ad hominem is legitimate and non-fallacious argument. From the middle of the 20th century number of scholars (Walton 1998, Groarke & Tindale, 2004, Salamon 2007, Woods, 2007, Mizrahi, 2010) argued that ad hominem argument should be examined and evaluated more precisely before dismissing it as irrelevant. Some authors even claim that in some cases ad hominem is especially relevant. Mizrahi (2010: 438) states that “argument traditionally recognized as ad hominem is especially relevant and legitimate in the cases of using the argument based on expert opinion. When undermining the credibility on an expert ad hominem is legitimate rebuttal to appeal to authority.” Walton (2007: 161) writes that “the ad hominem or personal attack, argument is now highly familiar in politics, especially in the use of negative campaign tactics in elections”. In this research we were interested in analysis of political discourse on the example of Parliamentary debate because it is believed that political speeches often rely on the ethos and credibility of the speaker and the “strategy of attacking the person falls under the umbrella of ethoic arguments that deal with some features of the character of the speaker.” (Tindale, 2007: 81). The main question in this research was to determine when ad hominem can be regarded as legitimate argument in political discourse and when it is irrelevant and fallacious. For the purpose of this research, parliamentary debate in Croatia was analyzed. Data included 10 debates during the period of one year (June 2011 until June 2012). Parliamentary debates were based on various topics: from deciding on weather to send more Croatian solders to Afghanistan or debating on laws which prevent and punish violence in school to debating on European Union. Argumentation analysis was based on finding ad hominem arguments and evaluating them in the context of debate. Results have showed that relevance of ad hominem depends mostly on the topic. When economy, finances and investments were discussed ad hominem arguments were for the most part legitimate. For instance, when deciding on a new president of a Croatian company for energy (Hrvatska Elektra) opponents argued that his competence is questionable, saying: “The last company he headed went bankrupt ; he left hundreds of people unemployed”. Or in the case of presenting budget, ad hominem arguments were made against the Minister of finances, evoking some of his business failures. On the other hand, results have showed that when discussing topics which are more concerned with Croatian national identity, independence and sovereignty and therefore more emotional, ad hominem arguments are logically irrelevant and fallacious. The best example is discussion on laws concerning national minorities in Croatia (especially Serbs) or European Union. In those examples, origin of the speaker is always an argument against the person. “Father of the speaker was the partisan, or chetnik, or ustasha...” Conclusion is that, emotional approach to topic results with increase of fallacious ad hominem arguments in debate.